The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41467-020-16157-0
|View full text |Cite
|
Sign up to set email alerts
|

Valence-programmable nanoparticle architectures

Abstract: Nanoparticle-based clusters permit the harvesting of collective and emergent properties, with applications ranging from optics and sensing to information processing and catalysis. However, existing approaches to create such architectures are typically system-specific, which limits designability and fabrication. Our work addresses this challenge by demonstrating that cluster architectures can be rationally formed using components with programmable valence. We realize cluster assemblies by employing a three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“… 60 63 Besides DNA-assisted NP crystals, DNA nanostructures have recently been harnessed as templates for the fabrication of versatile and arbitrary valence-programmable NP clusters thus opening up new avenues in customizing NP cluster geometry, composition, and application-specific properties. 64 …”
Section: Dna Molds Nanoparticle Lattices and Molecular Lithographymentioning
confidence: 99%
“… 60 63 Besides DNA-assisted NP crystals, DNA nanostructures have recently been harnessed as templates for the fabrication of versatile and arbitrary valence-programmable NP clusters thus opening up new avenues in customizing NP cluster geometry, composition, and application-specific properties. 64 …”
Section: Dna Molds Nanoparticle Lattices and Molecular Lithographymentioning
confidence: 99%
“…[88] In the recent studies, the group showed a new approach for creating designed clusters with symmetric and arbitrary arrangement of nanoparticles in space using reprogrammable 3D ball-like mesh DNA scaffold. [89] Recently, Chan and co-workers constructed a variety of novel Au-based hybrid nanoassemblies with the aid of DNA template. [90][91][92] Different from those in the single particle system, the biological delivery, and elimination properties could be tuned in the DNA assembled core-satellite (CS) superstructures (Figure 2a).…”
Section: Nanoparticle Clustersmentioning
confidence: 99%
“…“Chromatic” (“colored”) binding represents the addition of specificity into a nano‐object's binding coordination and valence, and this chromatic bond can be encoded through one or multiple (“polychromatic”) strands [4g, 5g, 21a] . In this manner, it is largely different than isotropic particle systems coated with specific DNA sequences and presents another dimension in DNA‐framed particle systems.…”
Section: Imparting Order Through Scaffoldsmentioning
confidence: 99%